A Screening Method for the ALK Fusion Gene in NSCLC - Murakami, Yoshiko; Mitsudomi, Tetsuya; Yatabe, Yasushi (Frontiers in Oncology, 2012)
Lung cancer research has recently made significant progress in understanding the molecular pathogenesis and even the treatment of lung cancer. Such achievements are directly utilized in clinical practice. Indeed, the EML4-ALK fusion in non-small cell lung cancer (NSCLC) was first described in 2007, and a molecularly targeted drug against the fusion was approved in 2011. However, lung cancer with the anaplastic lymphoma kinase (ALK) fusion constitutes only a small fraction of lung cancers; thus, efficient patient selection is crucial for successful treatment using the ALK inhibitor. Currently, RT-PCR, fluorescent in-situ hybridization (FISH) and immunohistochemistry are commonly used to detect the ALK fusion. Although FISH is currently the gold standard, there are no perfect methods for detecting the genetic alterations. This article discusses the advantages and disadvantages of the individual methods and possible criteria for selecting patients more likely to have the ALK fusion. If we can successfully screen patients, then ALK inhibitor treatment will be the best example of personalized therapy in terms of selecting patients with an uncommon genotype from those with the same tumor phenotype. In other words, it may offer a new challenge for current clinical oncology.